Role of EKC and PHH in Determining Environment Quality and their Relation to Economic Growth of a Country - Zomorrodi, Ahmad; Zhou, Xiaoyan (Asian Journal of Economics and Empirical Research, 2016)
Globalization, liberalization of international trade and recent economic developments have resulted in widespread pollution and therefore degrading environment quality in many countries over the world. This study tries to examine the role of Environmental Kuznets Curve (EKC) and Pollution Haven Hypothesis (PHH) in shaping the relationship between environmental quality and the economic growth of a country. To this end, a comparative overview of developing and developed countries across the world have been evaluated for their economic growth and the resultant impact on environmental quality, and their use of EKC and PHH to determine it. Descriptive analysis is used in the estimation. Results have shown that no clear conclusion can be determined as the role of EKC and PHH varies across economies, however both the theories are evident more in case of developing countries. The environmental quality depends on whether the country is developed or developing along with the imposition of stringent regulations as well as the propensity to act on the regulations effectively.